Response to Professor Hu Jinyu’s Letter [Response to Letter] - Kang X; Jin D; Ji H; An X; Zhang Y; Duan L; Yang C; Zhou R; Duan Y; Zhang Y; Sun Y; Jiang L; et al. (Drug Design, Development and Therapy)
Xiaomin Kang,1,2 De Jin,3 Hangyu Ji,1 Xuedong An,1 Yuehong Zhang,1 Liyun Duan,1 Cunqing Yang,1 Rongrong Zhou,1 Yingying Duan,1,2 Yuqing Zhang,1 Yuting Sun,1 Linlin Jiang,1,2 Fengmei Lian,1 Xiaolin Tong1 1Guang’anmen Hospital, China Academy of Chinese Medical Sciences, Beijing, People’s Republic of China; 2Beijing University of Chinese Medicine, Beijing, People’s Republic of China; 3Hangzhou Hospital of Traditional Chinese Medicine, Hangzhou, People’s Republic of ChinaCorrespondence: Xiaolin Tong, Guang’anmen Hospital, China Academy of Chinese Medical Sciences, No. 5, Beixiange, Xicheng District, Beijing, 100053, People’s Republic of China, Email tongxiaolin@vip.163.com Fengmei Lian, Guang’anmen Hospital, China Academy of Chinese Medical Sciences, No. 5, Beixiange, Xicheng District, Beijing, 100053, People’s Republic of China, Email 694397644@qq.com